2018
DOI: 10.1111/josh.12647
|View full text |Cite
|
Sign up to set email alerts
|

School‐Level Socioeconomic Status Influences Adolescents' Health‐Related Lifestyle Behaviors and Intentions

Abstract: Students from low ICSEA schools would benefit from additional support to improve dietary-related behaviors and intentions. More research is required to identify what targeted approaches will address sex differences in adolescents' lifestyle behaviors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 28 publications
2
16
1
Order By: Relevance
“…SSB consumption varied according to sociodemographic and school environmental variables. Similar to previous studies (28,29,47,48) , SSB consumption was higher among boys compared with girls and among adolescents from disadvantaged compared with advantaged schools. SSB consumption was also greater among adolescents in regular programmes compared with specialised programmes.…”
Section: Discussionsupporting
confidence: 89%
“…SSB consumption varied according to sociodemographic and school environmental variables. Similar to previous studies (28,29,47,48) , SSB consumption was higher among boys compared with girls and among adolescents from disadvantaged compared with advantaged schools. SSB consumption was also greater among adolescents in regular programmes compared with specialised programmes.…”
Section: Discussionsupporting
confidence: 89%
“…Prevention and lifestyle interventions for adolescents' obesity were primarily conducted through schools to reach a wide population, but the outcomes of many school-based interventions were equivocal [44]. A previous study reported that students from high schools with a high school-level socioeconomic status were more likely to eat breakfast and less likely to drink SSBs [20]. In contrast to the results in western countries, PUHSSs were more likely to have better lifestyle behaviours than IUHSSs in this study.…”
Section: Discussioncontrasting
confidence: 72%
“…Some studies have demonstrated that adolescents living in rural areas had a higher level of physical activity, shorter sitting time, less exposure to computers, video games and television, more calorie intake and less fruit and vegetable consumption compared with those living in the urban areas [16][17][18]. Limited studies have investigated the differences in students' lifestyle behaviours between schools in different socioeconomic districts [19,20]. Moreover, previous studies have explored the lifestyle behaviours of children and adolescents [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…These unhealthy behaviours may lead to a higher risk of noncommunicable diseases later in their lives (2)(3)(4)(5). The prevalence of these unhealthy behaviours is not evenly distributed across young people (6,7). Students attending vocational education have less favourable health practices than students attending higher secondary schools (8).…”
Section: Introductionmentioning
confidence: 99%